2017
DOI: 10.5863/1551-6776-22.1.48
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive List of Items to be Included on a Pediatric Drug Monograph

Abstract: OBJECTIVES Children require special considerations for drug prescribing. Drug information summarized in a formulary containing drug monographs is essential for safe and effective prescribing. Currently, little is known about the information needs of those who prescribe and administer medicines to children. Our primary objective was to identify a list of important and relevant items to be included in a pediatric drug monograph. METHODS Following the establishment of an expert steering committee and an environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…21,22 The process for developing the British National Formulary for Children and the Dutch Paediatric Formulary is aligned with the process for developing our child essential medicines list: collaboration; consulting expert clinical advisors, the literature, systematic reviews, consensus guidelines, reference sources and comments from readers; and continuous revision are important components. 23 The British National Formulary for Children also includes information in such areas as how to use the formulary, selecting suitable preparations, dosage selection and writing prescriptions. 21 Likewise, South Africa includes these details around the development process for their Standard Treatment Guidelines and Essential Medicines List for hospital-level pediatrics, as does India for their Essential Medicines List for Children of India.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The process for developing the British National Formulary for Children and the Dutch Paediatric Formulary is aligned with the process for developing our child essential medicines list: collaboration; consulting expert clinical advisors, the literature, systematic reviews, consensus guidelines, reference sources and comments from readers; and continuous revision are important components. 23 The British National Formulary for Children also includes information in such areas as how to use the formulary, selecting suitable preparations, dosage selection and writing prescriptions. 21 Likewise, South Africa includes these details around the development process for their Standard Treatment Guidelines and Essential Medicines List for hospital-level pediatrics, as does India for their Essential Medicines List for Children of India.…”
Section: Discussionmentioning
confidence: 99%
“…Since dosages guidelines were not part of the presented lists, this issue was discussed in depth with the medical doctors. The lack of evidenced‐based drug monographs containing information regarding paediatric prescribing is clearly a threat to safe and effective medicine use . This step will be very time‐consuming, will require national collaboration, was not feasible within the initial 3‐year funding and is an obvious limitation of this project.…”
Section: Discussionmentioning
confidence: 99%
“…A Delphi survey with 31 HCP from more than six continents by Kelly et al demonstrated that besides dosing information (licensed and off-label indications), formulations, adverse drug reactions, precautions, and drug-drug interactions should be included in a paediatric drug monograph [7]. Particularly the answers to the open-ended questions of the user test helped to adapt the PDIS to the needs of the German end-users, which were in line with the items identified by Kelly et al Another important finding of the online user test was the high demand for a dosage calculator.…”
Section: Evaluation Of the Prototype Pdismentioning
confidence: 99%
“…For some drugs and indications, data from, e.g., clinical trials are available, and a well-established, evidence-based use can be assumed. On the other hand, a paediatric license does not imply high-level evidence for the use in children and that the latest scientific data are integrated into the license [ 6 , 7 ]. Furthermore, off-label use leads to significant variability of therapeutic approaches [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation